2006
DOI: 10.4049/jimmunol.177.7.4627
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Natural IgM Production from Liver B Cells by Exogenous IL-18 Improves the Survival of Burn-Injured Mice Infected with Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is the most common bacterium of postburn infection. In the present study we investigated the immune mechanism of susceptibility to this type of postburn infection and also examined the efficacy of IL-18 treatment. C57BL/6 mice were challenged with P. aeruginosa on day 7 after burn injury. Although the burn-injured mice showed a poor survival rate after bacterial challenge, they retained their IFN-γ production. The burned mice showed lower serum IgM levels and a poor IgM response followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 57 publications
(55 reference statements)
0
44
0
1
Order By: Relevance
“…However, methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa, not E. coli, are the most common bacteria in postburn infections (11,34). In contrast to the response to E. coli infection, burn-injured mice retain IFN-␥ production against P. aeruginosa infection (23). Nevertheless, they also show poor survival because natural IgM production, which is crucial for preventing P. aeruginosa infection, is suppressed in the mice after burn injury.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…However, methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa, not E. coli, are the most common bacteria in postburn infections (11,34). In contrast to the response to E. coli infection, burn-injured mice retain IFN-␥ production against P. aeruginosa infection (23). Nevertheless, they also show poor survival because natural IgM production, which is crucial for preventing P. aeruginosa infection, is suppressed in the mice after burn injury.…”
mentioning
confidence: 92%
“…NOD-SCID (nonobese diabetic, severe combined immunodeficiency) mice (8 weeks old, 20 g; Charles River, Inc., Yokohama, Japan) were also used. As we previously described (1,22,23), mice were anesthetized using an intraperitoneal (i.p.) injection with pentobarbital (1 mg/mouse; Abbott Laboratories, North Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural IgM antibodies are constitutively secreted by B1 cells. Several elegant animal models have demonstrated the protective role of natural IgM against numerous viral, bacterial, and parasitic infections (Influenza, Pseudomonas aeruginosa, Plasmodium falciparum) and a worse outcome of patients with IgM deficiency [5][6][7]. IgM has an important role in the classical pathway of complement activation when complexed with antigens and its pentameric structure favors agglutination of the invading organism and its neutralization.…”
mentioning
confidence: 99%
“…Some investigations have indicated that burn-induced immunosuppression could be overcome through administration of select cytokines (Kinoshita et al, 2006), hormones (Kovacs et al, 2004), antioxidants (Cetinkalee et al, 1999), CpG oligonucleotides (Yabuki et al, 2010), and/or immunomodulating drugs like indomethacin (Choudhry et al, 2002) and cimetidine (Gharegozloo et al, 2004), as well as by surgical excision of the burn wound (Kovacs et al, 2004). We recently demonstrated that cimetidine restores burn-induced suppression of delayed-type hypersensitivity (DTH) responses at 10 days post-thermal trauma (Jafarzadeh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%